If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -1(5 + -1n) = 3(n + 8) n + (5 * -1 + -1n * -1) = 3(n + 8) n + (-5 + 1n) = 3(n + 8) Reorder the terms: -5 + n + 1n = 3(n + 8) Combine like terms: n + 1n = 2n -5 + 2n = 3(n + 8) Reorder the terms: -5 + 2n = 3(8 + n) -5 + 2n = (8 * 3 + n * 3) -5 + 2n = (24 + 3n) Solving -5 + 2n = 24 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -5 + 2n + -3n = 24 + 3n + -3n Combine like terms: 2n + -3n = -1n -5 + -1n = 24 + 3n + -3n Combine like terms: 3n + -3n = 0 -5 + -1n = 24 + 0 -5 + -1n = 24 Add '5' to each side of the equation. -5 + 5 + -1n = 24 + 5 Combine like terms: -5 + 5 = 0 0 + -1n = 24 + 5 -1n = 24 + 5 Combine like terms: 24 + 5 = 29 -1n = 29 Divide each side by '-1'. n = -29 Simplifying n = -29
| 5-2x-5=12 | | 7+n=5+3n | | X=3.166666667 | | 3x+20=2x+100 | | -3(x-3)=5-4x | | 4.00x+90.00=2.00(60+x) | | x-4-3x=-2x-8 | | -2n-3n=10 | | 7+n=5+n | | 2.3p-(21.2)=32.7 | | 2x+13-x+13=-2 | | 10x=14-x^2 | | -19.758+5.1p=3.2(3.1p-0.3) | | 4p-3+4=-3 | | -2(6+5)=-15-2 | | 30+B=14 | | 6(3X-6)=(6X+2) | | 15Y-1Y^2=15-1Y | | 4r-5r=-2 | | 6+10= | | 5x^2=28x | | -1=a-23 | | 4k-24=6(-8k-4) | | 2(4x-4)=-20-4x | | 6(x-2)=3x+3 | | 6*8=x | | 2x+45-23=180 | | 4x-8=x-7 | | 15-1Y=15Y-1Y^2 | | 2b+6b=-16 | | 5p-18=-301 | | 39-8x=-5(2x-5) |